Dimensional Changes of Yttria‐stabilized Zirconia under Different Preparation Designs and Sintering Protocols. Issue 8 (14th April 2020) - Ahmed, Walaa Magdy; Troczynski, Tom; Stojkova, Biljana Jonoska; McCullagh, Anthony P.; Wyatt, Chris C.; Carvalho, Ricardo Marins
Abstract: Purpose: To evaluate the linear and volumetric dimensional changes that occur throughout the fabrication process of monolithic 4.5‐6% yttria‐stabilized zirconia copings under the influence of different preparation designs and two sintering protocols. Materials and Methods: A titanium master die was fabricated using Atlantis core file implant‐abutment. Six copings were designed virtually according to different finish line offsets and coping thicknesses, with four equidistant occlusal posts for linear measurements. Zirconia copings were milled using IPS e.max ZirCAD LT zirconia blanks. The experimental groups according to the coping designs were the following: G1: 0.5 mm finish line offset, 0.5 mm thickness; G2: 0.5 mm finish line offset, 1.0 mm thickness; G3: 0.5 mm finish line offset, 1.5 mm thickness; G4: 1.2 mm finish line offset, 0.5 mm thickness; G5: 1.2 mm finish line offset, 1.0 mm thickness; G6: 1.2 mm finish line offset, 1.5 mm thickness. Six samples per group were sintered by standard sintering (SS) and the other six by fast sintering (FS). Linear and volumetric measurements were taken at the three fabrication stages (virtual design, milling stage, and sintering) by using an intraoral scanner and imported as the .stl file to Meshmixer software for analysis. Statistical analysis was performed by a linear mixed effect model via statistical software R (R Core team, 2018). Results: There was a significant interaction between the coping design group, stage of fabrication and sintering protocol on the linear (F = 4.451, p < 0.001) and volumetric (F = 2.716; p < 0.001) dimensional changes. Standard sintering G1 showed the smallest linear and dimensional changes among the groups compared to the reference design. Sintered copings had shrunk on average 1.32% within SS and 1.54% within FS linearly and 3.82% within SS and 3.90% within FS volumetrically compared to the initial design parameters. Conclusion: The linear and volumetric dimensional changes did not differ significantly between standard and fast sintering protocols, and the preparation designs had more influence on the dimensional changes compared to sintering protocols.